Review and commentary of the nutritional recommendations, weight management regulations, weight management practices, and the potential of disordered eating patterns in high school age wrestlers - Knox, C. (The Sport Journal, 2017)
The purpose of this article is to review the nutritional recommendations, the weight management practices, and the weight management regulations of high school wrestlers. Serving as a commentary on how these influences coupled with the perceived demand for lean body composition for better performance can relate to disordered eating patterns in high school wrestlers. Wrestling creates a high caloric demand while at the same time wrestlers practice restrictive dietary behaviors. Extreme weight loss behaviors performed by wrestlers have been observed. Nutritional recommendations are primarily made by athletic coaches who are not properly trained in nutrition and weight management. This can lead to the acceptance by the wrestler to practice poor behaviors related to food and nutrition. There is a need to properly evaluate and educate the coaches and athletes on nutrition, and weight management. Such education is necessary for the health of the athlete as they progress through the season, and through growth and development.